From "trying ECVET" to "putting ECVET into practice" : the CREDCHEM example - Eberhardt, Christiane [Verfasser] (My University, 2012)
This article reports about the main results of the ECVET pilot project "CREDCHEM". During the projects lifecycle 12 units for working in a laboratory were developed within the partnership. "Together these units make up a complete qualification in some countries whereas in other countries they represent parts of an occupational profile or an 'additional qualification'." The units where tested by 55 learners from Italy, Germany, Slovakia, Bulgaria and the Czech Republic who spent time abroad as part of the CREDCHEM project. (Extract, BIBB-Doku)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; G 2.5.4 Qualifizierungs- & Ausbildungskonzepte; I 2.2 Europa; Europäisches Leistungspunktesystem; Pilotprojekt; Modularisierung; Qualifizierung; Laborberuf; Europa